Centrosome hypertrophy in human breast tumors: Implications for genomic stability and cell polarity - Lingle, Wilma L. (The National Academy of Sciences, 1998)
The centrosome plays an important role in maintenance of cell polarity and in progression through the cell cycle by determining the number, polarity, and organization of interphase and mitotic microtubules. By examining a set of 35 high grade human breast tumors, we show that centrosomes of adenocarcinoma cells generally display abnormal structure, aberrant protein phosphorylation, and increased microtubule nucleating capacity in comparison to centrosomes of normal breast epithelial and stromal tissues. These structural and functional centrosome defects have important implications for understanding the mechanisms by which genomic instability and loss of cell polarity develop in solid tumors.